Copula bivariate probit models: With an application to medical expenditures - Rainer Winkelmann (University of Zurich, Department of Economics, 2011)
The bivariate probit model is frequently used for estimating the effect of an endogenous binary regressor (the treatment) on a binary health outcome variable. This paper discusses simple modifications that maintain the probit assumption for the marginal distributions while introducing non-normal dependence using copulas. In an application of the copula bivariate probit model to the effect of insurance status on the absence of ambulatory health care expenditure, a model based on the Frank copula outperforms the standard bivariate probit model.
Keywords: C35; I12; 330; bivariate probit; binary endogenous regressor; Frank copula; Clayton copula; Panel; Probit-Modell; Kopula (Mathematik); Theorie